Successful Management of Complex Congenital Cataract and Its Complication: A Case Report: Keberhasilan Tatalaksana Katarak Kongenital Kompleks dan Komplikasinya: Sebuah Laporan Kasus - Dian Estu Yulia; Yulika Harniza; Lia Amanda (eJournal Kedokteran Indonesia, 2022)
Management of cataract and its complication after surgery in a child with complex congenital cataract where accompanied by other ocular abnormality can pose a great surgical challenge. This case report described a case of an 18-year-old girl with slowly decreasing vision after undergoing surgery charity on the right eye (RE) around 4 months ago due to cataract which she had since birth. Best corrected visual acuity (BCVA) preoperatively of the RE and LE was 6/60 and 0,5/60 respectively. Ocular assessment was pseudophakia with Posterior Capsular Opacity (PCO) on the RE and cataract on the left eye (LE) accompanied by microcornea, nystagmus and coloboma of iris and retina on both eyes. Secondary posterior capsulotomy surgery was done on the RE and cataract extraction, Primary Posterior Capsulotomy (PPC) on the LE with Anterior Vitrectomy (AV) on both eyes. Last follow-up postoperatively showed a significant improvement of uncorrected visual acuity on her RE from 0.5/60 preoperatively to 6/30, meanwhile only subjective improvement of VA was found on her LE. This case can achieve visual improvement with promptly surgical treatment without complication and routine monitoring still needs to be done.